الخدمات المصرفية الالكترونية في اقتصاد انترنت الاشياء - قيمش, خولة; كتاف, شافية (University of Eloued جامعة الوادي, 2022)
Internet of Things technology is one of the most prominent technologies of the Fourth Industrial Revolution, which is based on the function of connecting different devices to each other and to the Internet The task is carried out without any human interference, so that it depends on big data and artificial intelligence systems. And so through this paper we wanted to highlight the benefits that can be achieved from applying Internet of Things (IoT) technologies in the banking sector and activating them on electronic banking services, as well as addressing the challenges that impede the achievement of this. The study finally concluded the positive implications of applying Internet of Things technologies to electronic banking services, whether at the operational level of the bank (planning, risk management, etc.), or for the client's satisfaction and knowing his needs precisely
Electronic banking in the Internet of Things economy
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: انترنت الأشياء، الخدمات المصرفية الالكترونية، القطاع المصرفي; Internet of Things; electronic banking; banking sector.